HIPEREALITAS DALAM IKLAN GO-JEK VERSI KAMU: KUNTI - Saniyah, Layyinatuzzahrah; Kartika, Bambang Aris; Wajihuddin, Wajihuddin (ROLLING, 2024)
Advertising is one of the media conveying information. In this contemporary era, humans always consume images from the mass media. Television or other online media is one of the mass media that contains advertisements. In order to arouse the desire to consume a product, advertisers make advertisements as creative as possible, one of which is the Gojek company. This ad presents a kuntilanak as a Gojek user, from here there is hyperality that occurs. The purpose of this study is to describe the depiction of visual hyperreality in the GO-JEK advertisement Your Version: Kunti. This research uses a qualitative approach with interpretative textual analysis. The results of this study show that the GO-JEK advertisement for Your Version: Kunti is a simulacra, which transforms concrete things (human version of Gojek users) into something abstract (Gojek users version of kuntilanak). In fact, the hyperreality in the GO-JEK advertisement for Your Version: Kunti is just an image that transcends reality.